رأس المال الفكري وعلاقته بتعزيز الرسوخ الوظيفي للعاملين بإدارات رعاية الشباب جامعة كفر الشيخ - عبدالجواد، أسماء عبدالحكيم فتوح (جامعة كفر الشيخ - كلية التربية الرياضية, 2022)
سعت العديد من المنظمات إلى تصميم برامج لجذب واستقطاب أفضل الموارد البشرية وتوفير أفضل السبل اللازمة لضمان رسوخها وبقائها في المنظمة، ويهدف البحث إلى التعرف على رأس المال الفكري وعلاقته بتعزيز الرسوخ الوظيفي للعاملين بإدارات رعاية الشباب جامعة كفر الشيخ من خلال التعرف على المتطلبات الواجب توافرها في رأس المال البشري بإدارات رعاية الشباب جامعة كفر الشيخ، والمتطلبات الواجب توافرها في رأس المال التنظيمي، والمتطلبات الواجب توافرها في رأس المال الهيكلي، والتعرف على دور الروابط في تعزيز الرسوخ الوظيفي للعاملين بإدارات رعاية الشباب جامعة كفر الشيخ، والتعرف على دور المواءمة في تعزيز الرسوخ الوظيفي للعاملين بإدارات رعاية الشباب جامعة كفر الشيخ، والتعرف على دور التضحية في تعزيز الرسوخ الوظيفي للعاملين بإدارات رعاية الشباب جامعة كفر الشيخ، والتعرف على دور التضحية في تعزيز الرسوخ الوظيفي للعاملين بإدارات رعاية الشباب جامعة كفر الشيخ، واستخدمت الباحثة المنهج الوصفي بالأسلوب المسحي كأحد أنماطه، وتم تطبيق البحث علي عينة عمدية من رؤساء إدارات رعاية الشباب بالكليات وأخصائي الأنشطة بإدارات رعاية الشباب بالكليات بجامعة كفر الشيخ وبلغ عددهم (50) فرد، وقد قامت الباحثة بتصميم استمارتين استبيان كأداة لجمع البيانات، الاستمارة الأولي اشتملت على (3) محاور تتضمن عدد (29) عبارة، والاستمارة الثانية اشتملت على (3) محاور تتضمن عدد (37) عبارة، وقد أسفرت نتائج البحث إلي ارتباط رأس المال الفكري في إدارات رعاية الشباب بجامعة كفر الشيخ بتوفير أعداد مناسبة من العنصر البشري المتميز يتم اختيارها وفقا للمؤهل العلمي والأكاديمي، يتطلب رأس المال الفكري رأس مال تنظيمي يساعد في رفع الكفاءة التنظيمية، يتطلب رأس المال الفكري توافر رأس مال هيكلي يساعد في وضع توصيف وظيفي يحدد مهام واختصاصات العاملين، محور دور الروابط أكثر تأثير بنسبة قدرها (58.53%) بينما حققت الخطوة الثانية لمحوري دور الروابط ودور المواءمة مجتمعين نسبة تفسير قدرها (81.04%) من التباين الكلي وبذلك حقق متغير دور الموائمة نسبة مساهمة قدرها (22.51%) كما توضح الحالة أو الخطوة الثالثة لمحاور دور الروابط ودور الموائمة ودور التضحية ومجتمعين نسبة تفسير قدرها (95.39%) من التباين الكلي وبذلك حقق متغير دور التضحية مساهمة قدرها (14.35%) وأوصت الباحثة بضرورة لالتزام بالتوصيف الوظيفي للعاملين بإدارات رعاية الشباب، الاهتمام بتوفير الحوافز المادية والمعنوية المناسبة للمتميزين، ضرورة التنوع في تطبيق أساليب التحفيز وتحقيق العدالة والمساواة مما يزيد من الرسوخ الوظيفي، أن تهتم إدارات الكليات بانتقاء الكفاءات المؤهلة واستقطاب الموارد البشرية وفقا لمتطلبات العمل، وترقية الكوادر وفقا للكفاءة والخبرة، إجراء العديد من الدراسات التي تتناول الرسوخ الوظيفي في المؤسسات الرياضية. Many organizations have sought to design programs to attract and attract the best human resources and provide the best means necessary to ensure its consolidation and survival in the organization. The good news in the youth welfare departments of Kafrelsheikh University, the requirements that must be met in the organizational capital, and the requirements that must be met in the structural capital, and identifying the role of links in enhancing the career stability of workers in the youth welfare departments at Kafrelsheikh University, and identifying the role of harmonization in enhancing the career consolidation of workers in the youth welfare departments Kafrelsheikh University, and to identify the role of sacrifice in enhancing the job consolidation of workers in youth care departments at Kafrelsheikh University. (50) individuals, and the researcher designed two questionnaires As a data collection tool, the first form included (3) axes containing (29) phrases, and the second form included (3) axes containing (37) phrases, and the research results resulted in the connection of intellectual capital in youth welfare departments at Kafrelsheikh University The availability of appropriate numbers of the distinguished human element, to be selected according to the scientific and academic qualifications. Intellectual capital requires organizational capital that helps in raising organizational efficiency. Intellectual capital requires the availability of structural capital that helps in developing a job description that defines the tasks and competencies of employees. The focus of the role of links is more An effect of (58.53%), while the second step for the axes of the role of links and the role of alignment combined achieved an explanation rate of (81.04%) of the total variance, and thus the variable of the role of alignment achieved a contribution rate of (22.51%), as the case or the third step shows for the axes of the role of links and The role of harmonization and the role of sacrifice, and together, an explanation ratio of (95.39%) of the total variance, and thus the variable role of sacrifice achieved a contribution of (14.35%), and the researcher recommended the need to adhere to the job description for workers in youth welfare departments, paying attention to Providing the appropriate material and moral incentives for the distinguished, the necessity of diversity in the application of motivation methods and achieving justice and equality, which increases job consolidation, that college administrations be interested in selecting qualified competencies and attracting human resources according to work requirements, and promoting cadres according to efficiency and experience, conducting several studies that deal with career consolidation in sports institutions.
Keywords: السياسات الإدارية -- الموارد البشرية -- الهيكل التنظيمي -- التمكين الإداري -- الجامعات المصرية